American Sand Wasp (suggested common name), Bembix americana Fabricius, 1793 (Insecta: Hymenoptera: Crabronidae: Bembicinae) - Marirose P. Kuhlman; Adam G. Dale (EDIS, 2024)
This article describes the identification, biology, and importance of the American sand wasps (Bembix americana Fabricius), which are a subspecies-complex of large, robust wasps in the subfamily Bembicinae. They nest gregariously in bare soil and provision their nests with flies (order Diptera). The females are progressive provisioners, meaning they continue to provide their developing larvae with prey until the larvae pupate. Males participate in a distinctive mating behavior called a “sun dance” in which groups of males fly low over nesting areas waiting for females to emerge so they can be the first to mate with them. Adults feed on flower nectar and can often be found visiting a variety of wildflowers. This species has a broad ecological range and can be found nesting in a variety of soil types and habitats.